Optimization of Husband and Wife Conflict Resolution in the People of Kebumen Regency Through Tajdidu An Nikah - Agus Salim (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
In Islamic jurisprudence tajdidu an Nikah is carried out for several reasons, namely because the husband wants to return to the wife who was divorced in a condition where she has not been intimated, the husband refers to the wife who was divorced by raj'i when her idah period has expired, the husband refers to the wife who asks for khuluk, and then there are doubts. whether or not the marriage contract is valid. An interesting thing is the phenomenon that occurs in the community in Kebumen district, where tajdidu and nikah are used as a resolution to conflicts between husband and wife who are constantly fighting. This phenomenon is interesting to discuss, it is known that in Islam husband and wife conflicts are resolved through tahkim, while tajdidu and nikah as previously adhered to are only intended for four things. Therefore, this article will try to discuss how tajdidu an nikah is practiced in Islamic law, what is the practice of tajdidu an nikah in Kebumen society, and how optimal tajdidu an nikah is as a way to resolve household conflicts. This research is empirical research using a normative approach, where the phenomenon of tajdidu and nikah in Kebumen society will be analyzed for its effectiveness and how the provisions of Islamic law in muamalah fiqh relate to the resolution of husband and wife disputes in the household.